Comparison of the concentration of heavy elements and their weekly absorption in consumed rice planted in different regions of Guilan province - Neda Vahaji; Mandana Tayefe; Mostafa Sadeghi (فصلنامه ابن سینا)
Background: Contamination of rice with heavy metals and its entry into the food chain can cause irreparable damage to human health and the environment. The purpose of this study was to compare the concentration of heavy elements and their weekly absorption in consumed rice which has produced in different regions of Guilan province. Materials and methods: In this study, Hashemi rice samples were in nine areas of Guilan province. To determine the level of contamination of rice to heavy metals, an induced plasma mass spectrometry device (ICP-MS) was utilized. One-way analysis of variance and the mean comparison based on Duncan test at 5% probability were carried out level for nine areas with control group (10 treatments) in three replications for the elements cadmium, lead, nickel, and chromium. Results: There was a significant difference among the studied areas in terms of concentration of heavy metals as well as a significant difference with control. In all areas, lead was higher than the permitted level (0.2ppm). Except for Rudsar, Kudeh, and Kumeleh, chromium was higher than the permitted limit (1ppm). The concentration of nickel in Rasht and Shanderman was higher than the limit value (0.6ppm). Cadmium was lower than permitted value (0.1 ppm) in all areas. It should be noted that based on the FAO/WHO standard, the measured values of all studied metals were tolerable for human in the permissible weekly level. Conclusion: Although tolerable weekly intake of evaluated metals by people through rice consumption was not higher than the permitted value, the consumption of other contaminated foods with heavy elements along with rice may lead to significant and irreparable effects.